Repeated weighting in mixed-mode censuses - Szymkowiak, Marcin; Wilak, Kamil (Economics and Business Review, 2021)
The main aim of the paper is to use the repeated weighting (RW) method on data from the National Census of Population and Housing 2011 (NCPH) and Labour Force Survey (LFS) to ensure consistency between margins of final tables derived from different statistical sources. This technique, based on different data sources, would ensure consistency between estimates in final output tables. This is the first application of the RW approach on data from official statistics in Poland. The results obtained by applying the RW method to data from the NCPH and additional surveys (e.g. LFS) may be used by Statistics Poland for the formulation of conclusions and recommendations for the upcoming census in 2021. The method may be also considered as an important step towards the production of timely and more detailed statistical information in Poland based on multi-source data infrastructure in general.